Emergence Dynamics of Kochia (Kochia scoparia) Populations from the U.S. Great Plains: A Multi-Site-Year Study. Issue 1 (5th September 2017) - Kumar, Vipan; Jha, Prashant; Dille, J. Anita; Stahlman, Phillip W.
Abstract : Evolution of kochia biotypes resistant to multiple herbicide sites of action is an increasing concern for growers across the U.S. Great Plains. This necessitates the development of integrated strategies for kochia control in this region based on improved forecasting of periodicity and patterns of kochia emergence in the field. Field experiments were conducted near Huntley, MT, in 2013 and 2014, and in Manhattan and Hays, KS, in 2013 to characterize the timing and pattern of emergence of several kochia populations collected from the U.S. Great Plains' states. The more rapid accumulation of growing degree days (GDD) resulted in a shorter emergence duration (E90 –E10 ) in 2014 compared with 2013 in Montana. Kochia populations exhibited an extended emergence period (early April through mid-July). Among all kochia populations, in 2013, Kansas-Garden City (KS-GC), Kansas-Manhattan (KS-MN), Oklahoma (OK), and Montana (MT) populations began to emerge earlier, with a minimum of 151 cumulative GDD to achieve 10% cumulative emergence (E10 values) in Montana. The New Mexico-Los Lunas (NM-LL) population exhibited a delayed onset but a rapid emergence rate, while the North Dakota (ND) and Kansas-Colby (KS-CB) populations emerged over a longer duration (E90 –E10 of 556 and 547 GDD, respectively) in 2013 in Montana. In 2013 at the two locations in Kansas, kochia populations exhibited a similar emergence pattern, with no differences in the time to initiate germination (E10 ), rate of emergence (parameter b ), or duration of emergence (E90 –E10 ). At Hays, KS, the GDD for E50 and E90 were less for ND compared with KS-MN and KS-GC local populations. In 2014 the KS-MN kochia population exhibited an early (ED10 value of 215 GDD) but a more gradual emergence pattern (E90 –E10 =526 GDD) in Montana. In contrast, OK and New Mexico-Las Cruces (NM-LC) populations had an early and a more rapid emergence pattern (E90 –E10 =153 and 154 GDD, respectively). Kochia in Montana exhibited two to four emergence peaks. This differential emergence pattern of kochia populations reflects the occurrence of different emergence "biotypes" and emphasizes the need to adopt more location-specific and diversified weed control tactics to manage kochia seedbanks.